Obesity-Related Genetic Variants and Hyperuricemia Risk in Chinese Men - Ma, Zhimin; Wang, Yunfeng; Xu, Chaonan; Ai, Feiling; Huang, Ling; Wang, Jieping; Peng, Ji; Zhou, Yanming; Yin, Meihua; Zhang, Shan; Yang, Xinghua (Frontiers in Endocrinology, 2019)
Objective: Obesity/metabolic syndrome and hyperuricemia are clinically associated. However, the association of obesity/metabolic syndrome-related genetic variants with hyperuricemia is not clear. Therefore, we assessed this association in Chinese men diagnosed with hyperuricemia in comparison to healthy controls. Methods: We genotyped 47 single nucleotide polymorphisms (SNPs) previously identified to be associated with obesity or metabolic syndrome in 474 adult males (aged ≥18 years) using multiplex polymerase chain reaction. Multivariate logistic regression was used to investigate the association between genetic variations and hyperuricemia. Stratified analyses were applied to further assess the associations. Results: The obesity-related SNP in MSRA rs545854 significantly affected the serum uric acid levels. In addition, the G-allele of rs545854 was positively associated with the risk of hyperuricemia [odds ratio (OR) = 2.80, 95% confidence interval (CI) = 1.19–6.64, P = 0.0188]. After adjusting the model for body mass index and central obesity, rs545854 was shown to be an independent factor increasing the risk of hyperuricemia (OR = 2.81, 95%CI = 1.18–6.70, P = 0.0196). Stratified analyses also showed a significant association between rs545854 and hyperuricemia among meat eaters (OR = 2.62, 95%CI = 1.09–6.26, P = 0.0308). Conclusion: The obesity-related SNP rs545854 was correlated with the serum uric acid level and risk of hyperuricemia in a male Chinese population. Therefore, men carrying this SNP could benefit from limiting their meat consumption to prevent hyperuricemia. These findings suggest an underlying genetic link between obesity and hyperuricemia worthy of further exploration.